Pengaruh Tax Avoidance terhadap Nilai Perusahaan Subsektor Processed Food dengan Leverage Perusahaan sebagai Variabel Moderasi - Prasanto, Shania Rizky; Widiyati, Dian (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
This study aims to test and analyze the effect of tax avoidance on firm value by considering corporate leverage as a moderating variable. The object of this study is companies in the manufacturing industry of the basic necessities sector (consumer non-cyclicals) processed food sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses a quantitative approach with panel data types and uses multiple linear regression methods in testing the hypothesis. From the results of the study, it can be concluded that tax avoidance has a significant negative effect on firm value. Corporate leverage is able to moderate and strengthen the relationship between tax avoidance and firm value. The limitation of this study lies in the use of samples that are only limited to companies in the processed foods sub-sector listed on the IDX in a certain time period. Therefore, in subsequent studies, it is hoped that samples from other sectors and different years can be developed to gain a more comprehensive understanding of the effect of tax avoidance on firm value with corporate leverage as a moderating variable.